Fruit and vegetable intake and vitamin C transporter gene ( SLC23A2) polymorphisms in chronic lymphocytic leukaemia. - Casabonne, Delphine; Gracia, Esther; Espinosa, Ana; Bustamante, Mariona; Benavente, Yolanda; Robles, Claudia; Costas, Laura; Alonso, Esther; Gonzalez-Barca, Eva; Tardón, Adonina; Dierssen-Sotos, Trinidad; Vázquez, Eva; et al. (European Journal of Nutrition, 2017)
Purpose: There is currently no convincing epidemiological evidence that fruit and vegetable consumption, the primary source of vitamin C, plays a role in chronic lymphocytic leukaemia (CLL) aetiology. We hypothesized that variations in vitamin C dietary intake as well as in genetic variability in vitamin C transporter gene SLC23A2 could explain some inconsistencies in the literature. Methods: Fruit/vegetable/vitamin C consumption from food frequency questionnaires and six low-penetrance genetic susceptibility polymorphisms in vitamin C transporter gene SLC23A2 (rs1715364, rs6133175, rs1776948, rs6139587, rs369270 and rs6052937) were examined in 434 CLL cases and 1257 randomly selected controls from primary care centres with genetic data of whom 275 cases and 1094 controls having both diet and genetic information. Logistic regression models were used to estimate odds ratio (OR) and 95 % confidence intervals (CI). Results: CLL patients were more likely to have a higher fruit consumption than controls (highest versus lowest quartile in g/day OR: 1.48; 95 % CI: 1.00 to 2.18; P = 0.03), whereas no associations were found with vegetable or total vitamin C intake. Based on log-additive models, rs6133175_A > G (OR: 1.19, 95 % CI: 1.00 to 1.41; P = 0.05) and rs1776948_T > A (OR: 1.20; 95 %CI: 1.01 to 1.41; P = 0.04) were associated with CLL. The haplogenotype analysis (rs1715364, rs6133175) supported the genotype results. No gene-diet interactions in CLL remained statistically significant after correction for multiple testing. Conclusions: These data suggest that both fruit intake and genetic marker in SLC23A2 may play an independent role in CLL biology.